Density Functional Theory for the Study of the Multimode Jahn-Teller Effect - Matija Zlatar; Maja Gruden-Pavlović; Carl-Wilhelm Schläpfer; Claude Daul (CHIMIA, 2010)
The Jahn-Teller (JT) theorem states that in a molecule with a degenerate electronic state, a structural distortion must occur that lowers the symmetry, removes the degeneracy and lowers the energy. The multideterminental-DFT method performed to calculate the JT parameters for JT active molecules is described. Within the harmonic approximation the JT distortion can be analyzed as a linear combination of all totally symmetric normal modes in any of the low symmetry minimum energy conformation, which allows the intrinsic distortion path (IDP) to be calculated, exactly from the high symmetry point to the low symmetry configuration. Results obtained by the approach described here give direct insight into the coupling of electronic structure and nuclear movements.